Correlation of HbA1c Levels with Diabetic Peripheral Neuropathy by Nerve Conduction Study – A Retrospective Observational Study - Suresh kannan; Thelengana Arikrishnan; Ram Mohan G; Shahitha. S (The Bioscan, 2025)
Background Diabetic peripheral neuropathy (DPN) is a common and disabling complication of type 2 diabetes mellitus (T2DM), often associated with poor glycemic control. While glycated hemoglobin (HbA1c) is a key marker of long-term glycemia, its precise relationship with objective electrophysiological parameters remains variably reported. This study aimed to evaluate the correlation between HbA1c levels and nerve conduction study (NCS) parameters in patients with T2DM and DPN. Methods Hospital-based retrospective observational study was conducted in a Tertiary Care Centre at Puducherry from March 1 to May 28, 2025. Seventy patients with confirmed T2DM, aged 30–80 years, who presented with neuropathic symptoms and underwent NCS were included. Patients with type 1 diabetes, thyroid dysfunction, vitamin B12 deficiency, or alcohol abuse were excluded. Clinical data, HbA1c values, and NCS parameters—including motor and sensory conduction velocity, amplitude, and latency—were extracted and analyzed. Pearson correlation was used to assess relationships between HbA1c, diabetes duration, and NCS findings. Results The mean age of patients was 59.19 ± 11.7 years; 61.4% were male. The mean duration of diabetes was 9.19 ± 5.53 years and the mean HbA1c was 8.05 ± 1.53%. Axonal neuropathy was the most prevalent pattern (52.9%), followed by mixed (31.4%) and demyelinating (15.7%). A significant negative correlation was found between HbA1c and multiple NCS parameters: motor NCV (r = -0.28, p = 0.0181), sensory NCV (r = -0.23, p = 0.0485), motor amplitude (r = -0.36, p = 0.0018), and sensory amplitude (r = -0.29, p = 0.0144). Motor and sensory latencies were positively correlated with HbA1c (r = 0.26 and r = 0.27; p < 0.05). No statistically significant correlations were observed between diabetes duration and any NCS parameter. Conclusion Elevated HbA1c levels were significantly associated with reduced nerve conduction velocity and amplitude, and increased latency, suggesting a strong link between poor glycemic control and the severity of diabetic peripheral neuropathy. HbA1c may serve as a useful predictor of neuropathic risk, supporting the need for strict glycemic management and early electrophysiological screening in patients with T2DM.